The value of virtual assets: The role of game characters in MMOGs - Tony Manninen; Tomi Kujanpää (International Journal of Business Science & Applied Management (IJBSAM), 2007)
Game character, or avatar, acts as the nexus of virtual assets that the player collects and produces while exploring online game worlds. What is the value of this virtual identity in the online game community? Furthermore, what are the components of play that provide added-value to the players? The evolution of Massively Multiplayer Online Games (MMOGs) has been dramatic for the past 30 years. What has remained stable, however, is the role of game characters as the main channel for value growth and perception. In this paper, we apply game studies background in order to offer implications that would contribute to the field of business. By using the motivational framework with the game characters as focal point, we will point out the specific value structures that emerge in contemporary MMOGs.
Keywords: 650; games; virtual worlds; virtual economies